Influence of Technological Factors on the Quality of Chitosan Microcapsules with Boswellia serata L. Essential Oil - Lauryna Pudziuvelyte; Aiste Siauruseviciute; Ramune Morkuniene; Robertas Lazauskas; Jurga Bernatoniene (MDPI AG, 2022)
Essential oils contain many volatile compounds that are not stable and lose their pharmacological effect when exposed to the environment. The aim of this study is to protect Boswellia serrata L. essential oil from environmental factors by encapsulation and determine the influence of chitosan concentration and types (2%, 4%; medium and high molecular weights), essential oil concentration, different emulsifiers (Tween and Span), and technological factors (stirring time, launch height, drip rate) on the physical parameters, morphology, texture, and other parameters of the generated gels, emulsions, and microcapsules. For the first time, Boswellia serrata L. essential oil microcapsules with chitosan were prepared by coacervation. Hardness, consistency, stickiness, viscosity, and pH of chitosan gels were tested. Freshly obtained microcapsules were examined for moisture, hardness, resistance to compression, size, and morphology. Results show that different molecular weights and concentrations of chitosan affected gel hardness, consistency, stickiness, viscosity, mobility, and adhesion. An increase in chitosan concentration from 2% to 4% significantly changed the appearance of the microcapsules. It was found that spherical microcapsules were formed when using MMW and HMW 80/1000 chitosan. Chitosan molecular weight, concentration, essential oil concentration, and stirring time all had an impact on the hardness of the microcapsules and their resistance to compression.